Physiological traits, cadmium bioaccumulation and biomass distribution in seven cocoa genotypes - Freire Carrera, Fausto; Carrillo-Zenteno, Manuel; Pincay-Ganchozo, Roger; Rendón-Holguín, Jair; Luna-Murillo, Ricardo; Vecilla-Nicola, Alberto; Reynel, Víctor; Tezara, Wilmer (Frontiers in Agronomy, 2025)
IntroductionCocoa plants tend to accumulate significant amounts of cadmium (Cd) in their beans and derived products due to their high affinity for Cd, which can pose challenges for commercialization. Research on the variations in Cd absorption capability among cocoa genotypes is still limited.AimsThis study assessed physiological traits, soil pH, soil electrical conductivity (EC), macronutrient concentrations, Cd bioaccumulation, and biomass distribution in seven cocoa genotypes (CCN-51, EET-103, IMC-67, POUND-12, EET-399, EET-95 and EET-400) grown in greenhouse.MethodsThe genotypes were arranged in a randomized block design with three replicates, assessing variables such as chlorophyll content, leaf gas exchange, pH, soil EC, macronutrient concentration, Cd uptake and transfer, Cd bioaccumulation, and dry root and shoot biomass.Results and discussionResults showed no significant differences in chlorophyll content and gas exchange between genotypes, although EET-103 exhibited a higher transpiration rate. A significant reduction in gas exchange occurred 80 days after sowing, associated with decreases in chlorophyll content and stomatal conductance. The soil displayed a strongly acidic pH (≤5.5) and high EC (6 dS m-1) across all genotypes, with no significant inter-genotype differences observed. Cadmium accumulation was nine times higher in the shoot than in the roots, with EET-95 showing a reducedCd uptake capacity, and EET-399 demonstrating limited Cd transfer from root toshoot.ConclusionThe genotype with the highest Cd absorption and shoot accumulation was CCN-51. Conversely, POUND-12 had the lowest Cd levels in both shoot and root, suggesting its potential as a reference genotype to limit Cd entry to aboveground tissues, especially in soils with elevated Cd concentrations.